Media Sosial Komunitas untuk Meningkatkan Eksistensi Komunitas dalam Wacana Politik Pemilu Presiden 2019 - Vera Yuni Astuti; Ahmad Toni (Indonesian Scientific Journal (Jurnal Ilmiah Indonesia), 2020)
This research discusses NET.Good People community in Jakarta, Bogor, Depok, Tangerang and Bekasi (Jabodetabek) as part of efforts to strengthen their existence in political discourse during the 2019 Presidential Election. The instagram-based NET.Good People community in Jabodetabek came up with a political discourse content to maintain the image of NET.TV in the community without taking side with one of the presidential candidate pairs but rather asking the public not to abstain from voting. This research uses qualitative approaches and Critical Discourse Analysis method with the variants of Norman Fairclough. The results of this research show that the NET.Good People community in Jabodetabek did not take side with one of the presidential candidate pairs in the 2019 election. However, this research highlighted the importance of community members to take part in politics without being an abstainer in the presidential election in line with the messages they have sent on the instragram. The instagram messages were neutral and substantively called on the public to vote in the 2019 presidential election for the sake of a better Indonesia in the future.